A two-in-one immunoassay biosensor for the simultaneous detection of Odontoglossum ringspot virus and Cymbidium mosaic virus - Lin, Wei-Ping; Wang, Wei-Jhen; Lee, Chia-Hwa; Jan, Fuh-Jyh; Wang, Gou-Jen (Sensors and actuators. B, Chemical, 2022)
This study proposes a highly sensitive and label-free electrochemical immunosensor that can simultaneously detect Phalaenopsis virus, Odontoglossum ringspot virus (ORSV) and Cymbidium mosaic virus (CymMV). First, a microhemisphere array nickel mold was made using the semiconductor lithography process combined with the electroforming process. Afterward, hot embossing was used to print the microhemisphere array on a polyethylene terephthalate film. Then, to prepare the detection electrode with a nano/micro-hybrid structure, a thin gold film was sputtered on the microhemisphere array surface, followed by successively immobilizing 1,6-hexanedithiol and colloidal gold nanoparticles on the surface of the gold film. Finally, the ORSV and CymMV antibodies were mixed and immobilized on the electrode using the self-assembled monolayer method to prepare the two-in-one sensing electrode. The ORSV and CymMV were simultaneously detected using electrochemical differential pulse voltammetry. The biosensor developed in this study has a detection limit of 0.5 ng/mL. Notably, the virus can be detected even after diluting the sap of the infected leaf 100 times. [Display omitted] •A two-in-one immune biosensor for the simultaneous detection of Phalaenopsis virus, ORSV and CymMV, was proposed.•The biosensor electrode consists a self-assembled monolayer of gold nanoparticles on a micro hemisphere array.•The biosensor developed can detect the individual ORSV and CymMV in 2 min with a detection limit of 0.5 ng/mL.•The virus can be detected even after diluting the sap of the infected leaf 100 times.